In vitro and in vivo Evaluation of Pharmacological Potential of Lasia spinosa Linn. (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Lasia spinosa Linn. (Family: Araceae) is an important medicinal plant, which is traditionally used for treatment of different human ailments. The present study was undertaken to evaluate the in vitro thrombolytic, antiinflammatory and in vivo analgesic and hypoglycemic potentials of n-hexane, chloroform and aqueous soluble fractions of methanol extract of L. spinosa whole plant. Additionally, phytochemical screening was carried out by qualitative tests, which confirmed the presence of alkaloids, glycosides, steroids, tannins, saponin in this plant. During in vitro thrombolytic assay, the aqueous fraction at a dose of 500 μg/100 μl showed the maximum 33.15% lysis of the blood clot, as compared to the standard streptokinase (80.10%). The in vitro anti-inflammatory test was performed by inhibition of egg albumin denaturation assay and RBC membrane stabilization method. The chloroform fraction exhibited maximum anti-inflammatory potential by inhibiting 51.53% denaturation of albumin and by inhibiting 54.8% hemolysis of RBC membrane against hypotonic solution. Analgesic activity was evaluated by tail immersion method for central mechanism and by formalin-induced lick test for peripheral mechanism in mice. In tail immersion method, all the solvent fractions of L. spinosa at a dose of 500 mg/kg body weight exhibited a significant (p